The Implementation of Emotional Intelligence and Spiritual Intelligence in Improving the Quality of Teaching in SDN 2 Jurang Jaler - Marwiyah Marwiyah; Abdul Malik; Muhammad Muhammad (Electronic Journal of Education, Social Economics and Technology, 2025)
The aim of this research is to explain the implementation of emotional intelligence and spiritual intelligence in improving the quality of teacher learning at SDN 2 Jurang Jaler. This research uses a qualitative approach with a case study type of research. Data sources were obtained from the principal and teachers at SDN 2 Jurang Jaler. The instruments used to collect data are observation sheets, interview sheets, and documentation tools. Data collection techniques use observation, documentation, and interviews. The data analysis technique uses the Miles and Huberman method which consists of 3 stages, namely data reduction, data display, and conclusion drawing/verification. The research results show that the implementation of emotional and spiritual intelligence in improving the quality of teacher learning can be done through 5 parts, namely: 1) learning planning, 2) learning implementation, 3) learning evaluation, 4) professional competence, and 5) self-intelligence. These five sections show that emotional intelligence and spiritual intelligence can improve the quality of teacher learning at SDN 2 Jurang Jaler. It is hoped that this research will become an important concern for every school to instill emotional and spiritual intelligence starting from new teachers to students. Because the main actor is the teacher in the learning process. Apart from that, this research becomes a reference for further research.